Education in the Gulf countries in the light of international indicators and the achievement of the fourth goal of sustainable development goals - Al-Harbi, Meaad Maish Salah; Al-badrni, Bader (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the reality of education in the Arab Gulf countries in the light of international indicators standards in order to achieve the fourth goal of the sustainable development goals during the period (2010-2021). International indicators for achieving the fourth goal of sustainable development goals using UNESCO reports, and the results of the study concluded that the highest percentage of achieving the indicators was the total absorption index for the last grades of the preparatory stage of general education for both sexes in the Kingdom of Saudi Arabia. It achieved a high level and is almost constant from 2016 until 2020, and in the year 2020, the Sultanate of Oman obtained the highest percentage, and the lowest applied indicator was the indicator of the participation rate in technical and vocational programs (15-24 years) by gender, and in light of these results, the study concluded: Indicators of global competitiveness in the field of education to achieve the desired goals, encouraging the Gulf countries to continue to obtain high global ranks, and to achieve the technical and vocational programs index, we suggest the establishment of institutes and courses that increase students’ acquisition of these skills, and accordingly the two researchers suggest increasing support for scientific research and development by conducting studies of the most important factors of success And the failure of applying competitiveness indicators, as well as comparing the application of the results of the Gulf countries with developed countries.